Knowledge and practice of patients with diabetes mellitus in Lebanon - Karaoui, Lamis R. (2018)
Background The objective of this study was to assess the knowledge and practice of Lebanese patients living with diabetes mellitus in regards to their diabetes self- management. Methods A cross-sectional study, conducted between January and June 2015, enrolled 207 urban adult patients with diabetes mellitus from community pharmacies while purchasing their diabetes medications. Their knowledge and self-management practices were assessed using a structured anonymous interview survey questionnaire. Results The mean age of the participants was 60.2 ± 15.5 years, and the Male/Female ratio was 1.38. The mean knowledge score was 2.34 ± 0.88 points (out of 6). Very few participants (17.4%) knew their current medication side effects. The mean practice score was 5.86 ± 1.77 points (out of 8). Only 15.9% of patients reported current physical activity. A multiple linear analysis showed that those with a university degree had a significantly higher knowledge (Beta = 0.448, p = 0.001) and practice score (Beta = 0.523 p = 0.047) than those with intermediate or primary schooling. Those who reported following a special diabetes diet had a higher knowledge score (Beta = 0.482, p < 0.001) than those who did not. Knowledge score and practice score were highly correlated (Beta = 0.844, p < 0.001). There was no significant differential by gender and age for knowledge and practice scores. Conclusions The knowledge and practice scores of patients with diabetes mellitus were not satisfactory. Well-targeted interventions are needed, such as improving the communication between the pharmacist and people living with diabetes. The observed low adherence to physical exercise among patients with diabetes should also be addressed.